Construction of Dual Curriculum in Indonesian Education System During the New Order Government - Muhammad Zuhdi (TARBIYA: Journal of Education in Muslim Society, 2015)
Abstract Indonesian education system, beside the fact that it has a single system with a single educational law, accommodates two different official curricula administered by two different ministries, i.e. The Ministry of Education and The Ministry of Religious Affairs. This kind of dual system was officially initiated by the New Order Government in 1970s.  Using the social constructionism as a perspective, this study tries to re-construct the debates on educational policies during the New Order Era. While the Era has passed, the policy of having dual system remains relevant.The study is conducted using a qualitative-historical method, meaning that data are gathered from various resources using the qualitative approach combined with the historical perspective. Data are collected from various written documents as well as interviews with some resource persons. General conclusion of the paper is that the dual curriculum system has existed before the New Order government took the power. The different is that the New Order Government made the dual system official, while the previous system did not recognize religious school as parts of formal education system. Abstrak Meskipun Indonesia memiliki satu sistem pendidikan nasional dan satu Undang-undang pendidikan yang berlaku, namun ada dua kementerian yang mengelola pendidikan, yaitu Kementerian Pendidikan dan Kementerian Agama. Inilah yang dimaksud dengan dualisme sistem pendidikan Indonesia. Awalnya, pendidikan Islam berada di luar system, sehingga dualism itu tidak begitu Nampak. Namun sejak tahun 1970an dualisme ini mulai mewujud seiring dengan diakuinya pendidikan Islam sebagai bagian dari sistem pendidikan nasional oleh Pemerintah Orde Baru. Tulisan ini mencoba merekonstruksi dualisme sistem pendidikan di Era Orde Baru dengan menggunakan metode kualitatif-hsitoris. Tulisan ini membuktikan bahwa sebenarnya dualisme pendidikan telah ada sebelum masa Orde Baru. Namun, di masa Orde Baru-lah dualisme itu muncul secara aksplisit, ketika pendidikan Islam diakui sebagai institusi resmi yang berbeda dengan pendidikan sekuler. How to Cite:  Zuhdi, M. (2015). Construction of Dual Curriculum in Indonesian Education System During the New Order Government. TARBIYA: Journal Of Education In Muslim Society, 2(1), 47-60. doi:10.15408/tjems.v2i1.1819. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v2i1.1819